Crafting the Bamasaba beyond the physical cut - Dipio, Dominica O; Literature Department. Makerere University (Kampala : Dominic Dipio Production, 2009)
Crafting the Bamasaba presents the ritual process of Imbalu (circumc ision) beyond the physical cut. This is the most important identity rit ual among the Bagisu. In the context of changing times and challenges h ow is Imbalu positioned in the community? These are some of the themes addressed.
Copyright:Dominic Dipio Production
Summary from the video container
Layout and design; Jeffrey Balemezi, Editing and authoring Africa Ci nema and Culture Company Ltd.
A Dominic Dipio film
Keywords: Rites and ceremonies; Circumcision -- Uganda